The Impact of Lifting Liquidity Constraints on the Distributions of Consumption, Assets, and Debts - Seok-Kyun Hur; Taeyoon Sung (Korea Development Institute (KDI), 2003)
This paper examines the distributional effect of loosening liquidity constraints on consumption expenditures, asset holdings and debts using two years of cross-section data sets (1996 and 2001). The data sets of our concern are unique in that they enable us to evaluate the consequences of the economic regime change following the currency crisis in Korea. Our findings indicate that (1) the loosened monetary regime after the crisis lifted the liquidity constraints as well as lowered various interest rates uniformly, (2) the less binding liquidity constraints contributed to the contraction of consumption inequality, which accounts for approximately 22.4% of the total reduction, and (3) the reduction of consumption inequality accompanied by the widened income inequality is attributed to easier access to debt financing.
Keywords: 330